posted by .

show that i (imaginary) is a zero of f (x)= x^3+ (3-i)x^2 - 4ix -1

Plug in i for x and add up the terms. You should get zero. Remember that i^2 = -1

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. pre calc

    Is there any complex numer that is equal to its conjugate?
  2. to bobpurlsey

    I had the same answer as you: except I subtracted i-i = 0 Given vectors A= (Axi + Ayj), B= (Byj+Bzk) and C= (Cyj + Czk). a) find the triple product of these vectors defined by A dot (BxC) in terms of the vector components. I get 0 …
  3. pre-calc

    If f(x)= x-B/x-A, f(2)=0, and f(1) is undefined, what are the calues of A and B?
  4. MAth!PLease Help!

    5. Find the x and y intercepts of each linear equation. Be sure to write your answers as ordered pairs. a.y=3x-6 b.6y=-x+2 Set x = 0 and y = 0 to find the intercepts. will that get me 2 thingys for each.?
  5. Chemistry

    Ok I think I figured this out but im not sure if its right please help. Thanks(= Determine the oxidation number for nitrogen in each of the following a)NH3 = -3 b)NO2-1 = 2 c)N2= 2 d)NO2Cl= 2 e)N2H4= 2 The first one is right. All must …
  6. MATH

    I'M IN 6 GRADE PLEASE EXPLAIN HOW TO RENAME FRACTIONS TO DECIMALS AS EASY AS YOU CAN You divide the fraction by the the number at the top by the number at the bottom and get a decimal For example 5 --- = 6 doesn't go into the 5 so …
  7. Precalc

    if a question says is -a a zero of (some equation) can you just plug in all the x's as -a and see if you get zero?

    Hi here is my question: Solve: (x-3)/x+3/x2=-6/x^2+2x For my solutions, I got -2 and 0, but the problem is, when I plug the numbers back in, I have zero in the denominator which I know you can't have. I'm not sure what I did wrong, …
  9. pre-calculus 11

    an object has a mass of m= 3x/4x^2 and density of d=x-1/2^2 where ve m/d and state any restrictions on the variable. So this simplifies to v=3x/2x-2 my question is the restriction i have found is x cannot be 1 which would make the …
  10. algebra

    Want to make sure I am doing this correctly. Use the Intermediate Value Theorem for polynomials to show that the polynomial function f(x)has zero between the numbers given. f(x)=3x^2-x-4 ; 1 and 2 3(1)^2-1-4= - 2 below zero 3(2)^2-1-4= …

More Similar Questions